Influence of Se vacancies on the electron energy spectrum transformation of 2H-NbSe₂ - Mamalui, A.A.; Andreeva, O.N.; Sinelnik, A.V. (Functional Materials, 2016)
The results of density functional calculations of 2H-NbSe₂ electron energy spectrum with Se vacancies at various concentrations are presented in the article. It is found that volume of the hole-like Fermi surface tends to decrease with increasing concentration of the vacancies. At vacancy concentrations corresponding to the beginning of the phase transition 2H-NbSe₂ -> 4H-NbSe₂ the disappearance of carrier group occurs, that is an electronic topological transition of order 2.5 takes place.